Peran Guru Akidah Akhlak dalam Penanggulangan Perilaku Menyimpang Peserta Didik Madrasah Aliyah - RD. Vadli; Nurul Hazairin; Al Hudori (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Education is a conscious and well-planned effort to create learning environments and processes that enable students to actively develop their potential, including spiritual and religious strength, self-control, personality, intelligence, noble character, and the skills needed for themselves and society. This study aims to examine the role of Akidah Akhlak teachers in addressing deviant behavior among students at Madrasah Aliyah Laboratorium, Jambi City. The research employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. The findings reveal that Akidah Akhlak teachers play their roles through three main approaches: preventive approaches, including habituation and the inculcation of moral values; curative approaches, such as guidance and counseling as well as moral advice; and repressive approaches, involving the application of educational sanctions. The obstacles encountered include environmental influences, lack of parental supervision, and students’ low level of religious awareness. The study concludes that various forms of deviant behavior occur at Madrasah Aliyah Laboratorium, Jambi City, influenced by multiple factors originating from family, environment, and individual characteristics. Overall, Akidah Akhlak teachers play a significant role in overcoming deviant behavior through integrated preventive, curative, and repressive strategies